2019
DOI: 10.1093/jas/skz210
|View full text |Cite
|
Sign up to set email alerts
|

Uterine and vaginal bacterial community diversity prior to artificial insemination between pregnant and nonpregnant postpartum cows1

Abstract: The present study evaluated the bovine vaginal and uterine bacterial community diversity and its relationship to fertility. Postpartum beef cows (n = 68) were synchronized beginning on day −21 and ending with timed artificial insemination (TAI) on day 0. Pregnancy was diagnosed 30 d after TAI. Uterine and vaginal flushes were collected on day −21, −9, and −2 for bacterial DNA extraction to sequence the V1 to V3 hypervariable regions of the 16S rRNA gene. Results indicated a decrease in the number of bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
46
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 25 publications
10
46
1
1
Order By: Relevance
“…The genus Lactobacillus was found at a low relative abundance through the estrous cycle. These results were in agreement with previous studies that used culture-independent methods to characterize the vaginal microbiota of ruminants (4,14). Here, differences in relative abundance throughout the estrous cycle were detected for 32 genera and 3 families.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The genus Lactobacillus was found at a low relative abundance through the estrous cycle. These results were in agreement with previous studies that used culture-independent methods to characterize the vaginal microbiota of ruminants (4,14). Here, differences in relative abundance throughout the estrous cycle were detected for 32 genera and 3 families.…”
Section: Discussionsupporting
confidence: 93%
“…These authors have suggested an intestinal origin for the vaginal microbes, explained by the anatomical proximity (5,12). Ault and colleagues have previously described differences in the abundance of Tenericutes and Acidobacteria in pregnant and non-pregnant post-partum cows with a higher abundance of these phyla in non-pregnant cows (14). The absence or lower abundance of the Tenericutes phylum in previous studies compared with the present study could be related to differences in breed, geographic location, diet, and age, among others (5,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enterobacteriaceae in the vaginal tract may come from the gastrointestinal tract due to the anatomy of the ewe's reproductive tract as described by other authors in the cow [25,26]. Here, we described that LAB CFUs are very scarce in the ewe's vagina independently of the time evaluated as previous studies reported using culture-independent method (16S rRNA sequencing) in ruminants [20,27]. Bacterial communities studied (Enterobacteriaceae and LAB) were highly fluctuating over time and between animals, as previously described by other authors in bovine uterus [28,29].…”
Section: Discussionsupporting
confidence: 62%